Dental students’ perception and knowledge regarding the importance of professionalism in dentistry: A cross sectional study - Faiza Ijaz, Adeela Mehboob Awan, Talha Nayab, Huma Tahir, Bilal Zaman Babar, Talib Hussain, Maryam Khurshid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Professionalism has been recognised as an essential component of dental practise since the twenty-first century. Various researchers have published definitions of professionalism, but the perception of dental students and graduates regarding professionalism in Pakistan has been limited. Objective: The main objective was to explore the awareness and importance of professionalism among the undergraduate dental students in Pakistan. Method: This cross-sectional research was carried out among the third and final year dental students from August to December 2021. Written consent was attained from all the study participants. Data was collected and statistically analysed using the Statistical Package for Social Sciences, Version 21. The Chi-square test is conducted to assess the association between the variables. Results: From a total of 201 participants, 95 males (47.3%) and 106 females (52.7%) were involved. Among these, there were 93 (46.3%) 3rd year and 108 (53.6%) 4th year dental students. In response to being asked to listen actively to patients, the majority of the males (72/6%) and females (91.5%) agreed. Similarly, for recognising the needs of patients, 84% of males and 91.5% of females agreed (p value 0.000). Regarding finding it difficult to meet patient requirements, 84% of males agreed while 43.2% of females disagreed (p value 0.000). The majority of the participants who kept records were males (73.6%) and females (90.4%). Conclusion: The study concluded that dental students had adequate knowledge and attitude regarding dental professionalism. The students not only listened attentively to the patients but were also punctual and showed compassion and care towards the patients.